Determination of Some Elements in Seeds of Rose Species by WDXRF Spectrometry - Ercisli, S.; Demir, F.; Budak, G.; Orhan, E. (Asian Journal of Chemistry, 2010)
The metals content in seeds of six rose species (Rosa canina L., Rosa dumalis subsp. boissieri L., Rosa dumalis subsp. antalyensis L., Rosa villosa subsp. villosa L., Rosa pisiformis (Christ) D. Sosn and Rosa pulverulanta Bieb.) which found in same collection orchard in Agricultural Faculty of Ataturk University were determined semi quantitatively by using Wave-dispersive X-ray fluorescence spectrometer (WDXRF). A qualitative analysis of spectral peaks showed that there were differences among species in terms of percentage of P, K, Ca, Mg, S, Ba and Sr in its seeds.